The making of the Iliad : disquisition and analytical commentary - West, Martin Litchfield (Oxford : Oxford University Press, 2011)
The making of the Iliad is intended for readers who have some knowledge of Greek and of Homer. After introductory chapters on the poet of the Iliad's date and homeland, the poetic traditions known to him, the way in which his work developed, and its early reception, Martin West provides a running commentary on the epic, distinguishing the different stages of the poet's workings, illuminating his aims and methods, and identifying techniques and motifs derived from ancestral Indo-European tradition or imported from the Near East.
Bibliografija: str. 432-434
Kazalo
Keywords: Homer -- Homerus; Ilijada - komentar